2022
DOI: 10.1063/5.0081902
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine-resolved optical spectroscopy of the A2Π ← X2Σ+ transition in MgF

Abstract: We report on hyperfine-resolved laser spectroscopy of the A2Π ← X2Σ+ transition of magnesium monofluoride (MgF), relevant for laser cooling. We recorded 25 rotational transitions with an absolute accuracy of better than 20 MHz, assigned 56 hyperfine lines, and determined precise rotational, fine, and hyperfine structure parameters for the A2Π state. The radiative lifetime of the A2Π state was determined to be 7.2(3) ns, in good agreement with ab initio calculations. The transition isotope shift between bosonic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Compared to Cr [36] or sintered SrF 2 [39] precursor targets, the yield from sintered MgF 2 precursor targets decays rapidly, dropping by roughly half after typically 100 ablation pulses. This has motivated us to begin construction of a CBGB based on the chemical reaction between the Mg metal and a fluorinated gas [22,40], which should stably produce high yields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to Cr [36] or sintered SrF 2 [39] precursor targets, the yield from sintered MgF 2 precursor targets decays rapidly, dropping by roughly half after typically 100 ablation pulses. This has motivated us to begin construction of a CBGB based on the chemical reaction between the Mg metal and a fluorinated gas [22,40], which should stably produce high yields.…”
Section: Methodsmentioning
confidence: 99%
“…An upper limit on the spontaneous decay rate of the MgF A 2 1/2 state was recently reported with approximately 4% fractional uncertainty in Ref. [22]. There, was determined by measuring laser-induced fluorescence as a function of laser frequency and extrapolating the fitted Lorenzatian linewidth to zero power.…”
Section: Introductionmentioning
confidence: 95%
“…Its level diagram is illustrated in figure 9(a). MgF has received much interest recently as a good candidate for molecular cooling and trapping [83][84][85][86], largely because its light mass, large scattering rate (Γ XA /2π = 22 MHz), and high wavenumber/short wavelength of the cycling transition (λ XA = 359 nm) all enable large deceleration. For example, a max ∝ ℏk XA Γ/m is 15x higher for MgF than SrF.…”
Section: Mgfmentioning
confidence: 99%
“…Slow beam velocities in the laboratory frame and a wide applicable temperature range are important characteristics of buffer gas cooling. Currently, numerous spectroscopic studies using buffer gas cooling have been reported. …”
Section: Introductionmentioning
confidence: 99%